2011
DOI: 10.1021/bm200804j
|View full text |Cite
|
Sign up to set email alerts
|

pH and Reduction Dual-Sensitive Copolymeric Micelles for Intracellular Doxorubicin Delivery

Abstract: This study develops novel pH and reduction dual-sensitive micelles for the anticancer drug doxorubicin (DOX) delivery owing to the fact that the tumor tissues show low pH and high reduction environment. These sub-100 nm micelles present a core-shell structure under physiological conditions, but quickly release the loaded drugs responding to acidic and reductive stimuli. With disulfide bonds in each repeat unit of poly(β-amino ester)s, the novel copolymer was synthesized via Michael addition polymerization from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
205
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(209 citation statements)
references
References 49 publications
(83 reference statements)
3
205
0
1
Order By: Relevance
“…Within the last decade, persistent efforts have been made in the development of stimuli-responsive drug delivery systems that can, when exposed to external stimuli, produce physicochemical changes that favor drug release at the target site. Depending on the target, typical biological stimuli have been exploited for triggered drug release including temperature [1], pH [2][3][4], magnetic field [5,6], redox potential [7][8][9], enzymes [10][11][12] or two parameters at the same time [13][14][15]. pH controlled release systems are particularly more interesting because we can find physiologically the pH gradients relevant for drug targeting.…”
Section: Introductionmentioning
confidence: 99%
“…Within the last decade, persistent efforts have been made in the development of stimuli-responsive drug delivery systems that can, when exposed to external stimuli, produce physicochemical changes that favor drug release at the target site. Depending on the target, typical biological stimuli have been exploited for triggered drug release including temperature [1], pH [2][3][4], magnetic field [5,6], redox potential [7][8][9], enzymes [10][11][12] or two parameters at the same time [13][14][15]. pH controlled release systems are particularly more interesting because we can find physiologically the pH gradients relevant for drug targeting.…”
Section: Introductionmentioning
confidence: 99%
“…injection. Reduction and pH dual-sensitive SCL micelles were developed via self-assembly of aldehydecontaining P(OEGMA-co-p-(methacryloxyethoxy)benzaldehyde)-b-PCL diblock copolymer in NH 4 OAc buffer followed by cross-linking using difunctional dithiolbis (propanoic dihydrazide) (25). These dual-sensitive SCL micelles, although greatly retarded CPT release at pH 7.4, exhibited the fastest CPT release in response to 10 mM DTT at pH 5.0, which was comparable to that of NCL control.…”
Section: Reduction-sensitive Reversibly Scl Micelles and Polymersomesmentioning
confidence: 99%
“…Many previous studies have reported that drug delivery vehicles with pH-sensitive chemical bonds accelerate drug delivery and cause release at a lower pH. 16,17 Iron oxide nanoparticles (IONPs), a promising magnetic resonance imaging (MRI) agent, are extensively used in the field of cancer theranostics; they facilitate the description of targeted therapeutic drugs and the diagnosis of the lesion areas. 18,19 Researchers have verified that external magnetic induction allows DOX-containing nanoparticles to preferentially concentrate at the tumor site, and thereby increase the drug levels for an enhanced therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%